COST VOLUME PROFIT METHOD FOR PROFIT PLANNING ANALYSIS BASED ON ISLAMIC PERSPECTIVE - Nur Eka Mauliyah; Anisa Maulida; Liona Efrina; Mohammad Azmi; Parassela Pangestu Primadiva (Faculty of Economic and Social Science, Universitas Islam Negeri Sultan Syarif Kasim, 2025)
This MSME is a sector that can help develop the economy in various countries. MSMEs also often ignore the right profit planning for their MSMEs. The profit planning used by managers is the Cost Volume-Profit method. Profit planning is not assessed in terms of its material but is assessed based on an Islamic perspective, in order to bring blessings and prosperity to humans. The aim is to analyze profit planning in the MSME of tea bags of Sedap Malam in Pasuruan Regency using the Cost–Volume-Profit method and to analyze profit planning from an Islamic perspective. The approach and The type used in this study is descriptive qualitative. Data collection was carried out through observation interviews, and documentation. The results of this study are that of profit planning Implemented by the MSME Teh Celup Bunga Sedap Malam is still simple, the profit planning is carried out by the MSME is still not in accordance with the Cost-Volume-Profit (CVP) method and the calculation of its costs is not all included in the management of profit planning. And profit planning based on an Islamic perspective on the Tuberose Flower Tea Bag UMKM is in accordance with Islam, namely halal, not hoarding, not causing harm, and not deceiving.